Polymer‐Assisted Compressed Flux Growth: A Universal and High‐Yield Method for Dimension‐Controlled Single Crystals. Issue 12 (7th February 2023) - Ge, Chao; Zheng, Xiaoxin; Guo, Qing; Liu, Yang; Tao, Xutang
Abstract: Single crystals possess the most perfect and stable morphology and represent the intrinsic and upper limits of performance when integrated into various application scenarios. However, for a large portion of the newly emerging low‐dimensional and molecular materials, the mass production of crystals with a desirable shape is still challenging. Here, a universal and high‐yield method to grow functional single crystals with controlled dimensions is provided that can be directly integrated into a device. By utilizing a polymeric flux in combination with a compressed growth space, numerous materials can be grown into size‐controllable single crystalline flakes, with millions produced in one batch. This scalable growth method shows promise for the large‐scale integration of micro‐single‐crystals as functional components, as exemplified by the construction of a 5 in. field‐effect transistor array. Abstract : A high‐yield crystal growth method utilizing a polymer flux in a compressed growth space is invented to cast molecules or precursors into dimension‐defined single crystals. This compressed flux growth is universally applicable to various materials and scalable to mass production, and the grown single crystals can be directly integrated into electronic devices.